Genuine supramolecular isomers based on Y-shaped pyridinedicarboxylate ligands with distinct topology: 2D 63 layer, kgd layer to 3D rtl net. Issue 12 (16th February 2016) - Hou, Juan-Juan; Li, Xiao-Qing; Tian, Bao-Qiang; Zhang, Xian-Ming
Abstract : Three genuine supramolecular isomers with an identical formula of [Co(cpna)(H2 O)2 ] (1a, 1b and1c ) have been synthesized by adjusting the relative molar ratio of Y-shaped ligand H2 cpna : CoCl2 under solvothermal conditions. Abstract : Three genuine supramolecular isomers with an identical formula of [Co(cpna)(H2 O)2 ] (1a, 1b and1c ) [H2 cpna = 5-(4′-carboxyl-phenyl) nicotinic acid] have been synthesized by adjusting the relative molar ratio of Y-shaped ligand H2 cpna : CoCl2 under solvothermal conditions. Isomer1a possesses a two-dimensional (2D) 6 3 - hcb layer, in which the central Co(ii ) adopts trigonal bipyramidal geometry.1b and1c contain the same edge-shared dimeric SBUs, which are further ligated by cpna 2− ligands to form 2D (3, 6)-connected (43)2 (4 6 ·6 6 ·8 3 )- kgd layers and a 3D (3, 6)-connected (4·6 2 )2 (4 2 ·6 10 ·8 3 )- rtl net, respectively. The coordination modes of the cpna 2− ligand in1b and1c are the same, indicating that only the difference in the dihedral angles of the pyridine and phenyl rings contributes to different isomers. Magnetic investigation indicates ferromagnetic interactions between Co(ii ) ions in edge-shared dimeric SBUs.